A Method to Encode the Fingerprint Minutiae Using QR Code (Journal of the College of Basic Education, 2022)
Today, computers and mobiles devices become an essential part that people use to perform a major part of their daily activities. Those devices sometimes become meaningless without being connected to the internet. In addition, people exchange tens of their data cross multiple devices that are connected remotely using internet, the thing that make such data are exposed to be captured. Hence, to overcome such concerns, there is a big necessity to continuously develop new methods to mitigate the threat of data capturing by anonymous people. In this research, we present a method to encode human fingerprint using quick response code (QR Code). The method involves extracting the fingerprint minutiae which depicts the most important features of fingerprint, then that features are turned into image of QR Code format. This method ensures transferring a data with good level of safety since the real data are difficult to be guest. To make the process more complicate, we encrypted the fingerprint features by using (AES) encryption method which make the data meaningless event when they captured by anonymous intruders. After method implementation, the values of PSNR and MSE are calculated to evaluate the performance by comparing the original image with the reconstructed one. The results of the method proved that encoding the fingerprint using QR Codes can be successfully performed and utilized with different applications